Thoughts of a wingless butterfly - Mercedes Fraile Bravo (Universidad de Alicante, 2012)
Introduction. The protagonism acquired by Care has shown up even in situations as determining as women's invisibility. The attribution of tipically feminine roles against the roles of control oposition, activity force and dominion attributed to the male genre, reinforce this fact. The aim of this work is to demonstrate how Cultural Competence proposes a series of interventions which, from the perspective of transculturality, offer solutions and confirm the circumstance of invisibility and genre difference that occurs even after an increased women's educational and cultural level. The present story emerges from the anonimous thoughts of a middle-aged woman educated in a sexist environment to become an ideal mother and wife and comply with all the roles reserved to women in a traditional education. Methodology and results. Deep interview was used as activities for the intervention "Reminiscence therapy", within the Care Plan determined for a diagnose of "lack of hope". Conclusions. The conclusions deal with the role that genre plays in couples' relationships and in children's education, showing the influence of the social structure that impregnates all perpectives in life: publicity, education, etc, and confirms its impact on aim achieving towards genre equity.